Genetically informed, multilevel analysis of the Flynn Effect across four decades and three WISC versions - Giangrande, Evan J.; Beam, Christopher R.; Finkel, Deborah; Davis, Deborah W.; Turkheimer, Eric (Child development, 2022)
This study investigated the systematic rise in cognitive ability scores over generations, known as the Flynn Effect, across middle childhood and early adolescence (7–15 years; 291 monozygotic pairs, 298 dizygotic pairs; 89% White). Leveraging the unique structure of the Louisville Twin Study (longitudinal data collected continuously from 1957 to 1999 using the Wechsler Intelligence Scale for Children [WISC], WISC–R, and WISC–III ed.), multilevel analyses revealed between‐subjects Flynn Effects—as both decrease in mean scores upon test re‐standardization and increase in mean scores across cohorts—as well as within‐child Flynn Effects on cognitive growth across age. Overall gains equaled approximately three IQ points per decade. Novel genetically informed analyses suggested that individual sensitivity to the Flynn Effect was moderated by an interplay of genetic and environmental factors.